PENERAPAN BAGI HASIL AKAD MUZARA’AH PADA PETANI PADI DIKELURAHAN INEBENGGI KECAMATAN MOWEWE KABUPATEN KOLAKA TIMUR - Kasmawati Kasmawati; Nur Rahmah; Syamsuddin B (Jurnal Syariah Hukum Islam, 2020)
The muzara'ah contract which is based on the principle of cooperation using the profit sharing method is the calculation of the share of the net income from the total income after deducting the costs incurred to obtain income. If you experience a loss or crop failure, you will bear all the losses, namely the temporary cultivator who owns the land regardless of the loss because everything is the cultivator. Meanwhile, the muzara'ah agreement explains that the advantages are shared and the losses are shared. Therefore, there are differences of opinion between theory and practice, so that researchers still do not understand about cooperation on the muzara'ah contract The formulation of the problem in this study are: How is the management of muzara'ah contracts on agricultural products in Inebenggi Village, Mowewe District, East Kolaka Regency, How is the muzara'ah sharing system for agricultural products in Inebenggi Village, Mowewe District, East Kolaka Regency and How is the Application of Profit Sharing What the People in Inebenggi Village, Mowewe Subdistrict, East Kolaka Regency Embrace Is As Recommended. The objectives of this research are: To determine the management of muzara'ah contracts on agricultural products in Inebenggi Village, Mowewe District, East Kolaka Regency, To determine the muzara'ah profit sharing system for agricultural products in Inebenggi Village, Mowewe District, East Kolaka Regency The Profit Sharing That Is Adhered to by the Community in Inebenggi Village, Mowewe District, East Kolaka Regency Is As Recommended. The research method used is a qualitative research with a descriptive type that is objected to the application of the muzara'ah contract yield to rice farmers in Inebenggi Village, Mowewe District, East Kolaka Regency. Data collection techniques include observation, interviews and documentation on the owners of capital / land and tenants. Data analysis techniques used are data reduction, data triangulation, data presentation, drawing conclusions and verification. Based on the results of the study, it was concluded that the profit sharing carried out by the community (capital owners and smallholders) in Inebenggi Village, Mowewe District, East Kolaka Regency was in accordance with the profit sharing proposed by the Islamic Shari'at namely Al-muzara'ah